Dampak Kebijakan Penertiban Peredaran Minuman Beralkohol di Kota Jayapura - Elokpere, Andius; Silo, Akbar (JURNAL EKOLOGI BIROKRASI, 2024)
The article discusses the impact of controlling the circulation of alcoholic beverages in Jayapura City. The research conducted uses a descriptive qualitative research approach, including direct observation, interviews, and literature studies to collect data. The analysis of the data was done through data reduction, presentation, and drawing conclusions. The findings of the study reveal that the implementation of local government policies in controlling the circulation of alcoholic beverages in Jayapura City has been ineffective. The city government does not enforce the local policy of local regulation No. 15 of 2013, which prohibits the production, distribution, and sale of alcoholic beverages. Instead, the government issued its own policy, Mayor Regulation No. 8/2014, which focuses on the supply, control, and supervision of alcoholic beverages. However, the control and supervision have been poorly executed, resulting in the widespread availability of alcoholic beverages and liquor, with even minors and young adults being able to purchase and consume them. As a result, this situation has disrupted the social life of the community in Jayapura City.